Malaysia's defeat of armed communism : the Second Emergency, 1968-1989 - Ong, Weichong (New York : Routledge, 2015)
'The Malayan Communist Party's (MCP) decisive defeat in 1960 led many academics and counterinsurgency (COIN) experts to overlook the resurrection of its armed struggle in 1968. Most scholars continue to regard the so-called'Second Emergency' in Malaysia (1968-1989) as a non-event, and most of the recently published work on the MCP tends to focus on the earlier Malayan Emergency (1948-1960). This book looks at the Second Emergency through recently released archival material from the National Archives in London, the National Australian Archives and the Australian War Memorial, as well as interviews with military and diplomatic officers from the UK and Thailand'--
1. Introduction : why the Second Emergency matters -- 2. Fighting big wars and small wars : approaching COIN and Maoist revolutionary war -- 3. Strategy of the CPM's revived armed struggle : retreat, reform and revival (1948-1981) -- 4. The role of mass persuasion in revolutionary war -- Response of the post-colonial state : the persistence of the colonial COIN template (1968-1981) -- 6. The making of a winning state : lessons in post-colonial COIN and nation-building -- 7. Conclusion.
Includes bibliographical references and index.
Also available in print edition.
Mode of access : World Wide Web.
Keywords: Malayan Communist Party -- History; Communism -- Malaysia -- History; Insurgency -- Malaysia -- History; Counterinsurgency -- Malaysia -- History; Malaysia -- History -- 20th century; Electronic books